(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to explore the role of green Creative in green insurance and securing its financing. It also aims to provide green innovation’s conceptual framework, highlights its objectives and importance including (the use of renewable energy sources, enhancing resource usage, developing eco-friendly products, reducing waste and pollution, and improving agriculture). Furthermore, the research seeks to define green insurance and its characteristics represented in: providing insurance for green projects, covering environmental risks, motivating companies to improve their green performance by offering insurance discounts, and developing green insurance products. In order to achieve the desired objectives, National Insurance Company in Iraq, which provides various forms of insurance including agricultural insurance, was conducted in this research. A descriptive-analytical approach was adopted. A survey was distributed randomly to (40) workers of middle and senior management in National Insurance Company. SPSS statistical tests were done such as (mean, standard deviation, Pearson correlation, and simple linear regression). The research was divided into four sections. The first focused on the general framework and research methodology, the second included the fundamental theoretical concepts of the research variables, section three encompassed the practical aspect of the research and the tested its hypotheses, while the fourth section concluded that there is a relationship between the elements of green innovation, whether collectively or individually, and green insurance in the researched company, and demonstrated that green insurance increases green sectors’ investment, preserving green projects and enhancing their performance. Finally, the researcher recommended green innovation in all fields and ways that fit the natural environment to achieve sustainable production and consumption. In addition to that, that researcher, recommended to enhance insurance sector’s awareness, particularly in green insurance sector, and get the benefit from advanced countries experiences.